SOCIO-CULTURAL VALUES AND CHILDREN’S RIGHTS IN CALABAR - OFFIONG, EKWUTOSI ESSIEN; UDUIGWOMEN, GODSPOWER ANDREW (Society Register, 2021)
This paper on Socio-Cultural Values and Children’s Rights in Calabar analyses the history and value system associated with child upbringing in the city of Calabar. Communalism, which ensured child socialisation from birth, was a common practice in Calabar like in other areas of Africa and Nigeria until European incursion and eventual introduction of capitalism during colonial times. This change resulted in the diminishing of communal lifestyle and reduction of family sizes to nuclear forms. It also necessitated the population increase and related social problems. Although historical in content and analysis, the paper adopted the multidisciplinary approach of reconstruction with data gleaned from primary and secondary sources. Findings showed that right from pre-colonial times, inhuman practices that abused children’s rights like child pawning and killing of twins characterised this study area. Population increase and the rise of urban poor and slums resulted in the breeding of abused children, with most homeless on the streets of Calabar. Witchcraft labelling and child trafficking were also highlighted as other significant and recurring causes of child abuse in Calabar. This paper concluded by reiterating that as Calabar flouts its status as a ‘restful city’, children must not be denied of this ‘restful’ lifestyle. Child rights must be implementable and child right violators prosecuted.